Characterization and evaluation of local samosir shallot (Allium ascalonicum L.) morphology at some accessions in Bakti Raja Districts - Joindida Frensisco Sianipar; Mariati Sinuraya (Universitas Sumatera Utara, 2016)
The aim of this research was to identify the morphological characteristics of several local Samosir shallot which was conducted in Bakti Raja, Humbang Hasundutan district i.e. Siunong-unong Julu, Marbun Dolok, Simamora, Marbun Toruan, Sinambela-Simanulang and Simangulampe start from July till August 2015. This research was implemented by using randomized block design non factorial with 3 replicants. The parameters observed were time flowering, leaves colour, bulbs shape, bulbs colour, plant length, leaves number, tillers number per clump, wet bulbs weight, dry bulbs weight, bulbs number per clump, diameter of bulbs, 100 bulbs dry weight, wet-dry bulbs weight decrease. The result of research showed local Samosir shallot in six accession in Bakti Raja districts have narrow kuantitative related. The morphological differentiator characteristic of the accessions was wet bulbs weight. The potential yields of each accession shown that the shallot from Marbun Toruan has the highest yields potential i.e 15,20 ton/ha then Siunong-unong Julu i.e 12,00 ton/ha, Simangulampe i.e 11,93 ton/ha, Simamora i.e 11,76 ton/ha, Sinambela-Simanulang i.e 11,36 ton/ha and Marbun Dolok i.e 11,07 ton/ha wet bulbs.